Crystallinity depends on choice of iron salt precursor in the continuous hydrothermal synthesis of Fe–Co oxide nanoparticles - Richard Palmer (RSC Advances, 2017)
A series of Fe–Co oxide nanoparticles (NPs) were prepared by a continuous hydrothermal method using iron nitrate and ammonium iron citrate as alternative iron precursors. The crystallinity, Fe/Co composition and element spatial distribution in the synthesised NPs were investigated using X-ray diffraction (XRD), aberration-corrected scanning transmission electron microscopy (ac-STEM) imaging, energy-dispersive X-ray spectroscopy (EDX) and electron energy loss spectroscopy (EELS). Strong dependence on the choice of iron salt was observed. We demonstrate that the presence of ammonium citrate markedly improves the crystallinity of the NPs; an ordered cobalt ferrite alloy is formed. We suggest this is due to the formation of a homogenous reaction environment during the thermal decomposition of ammonium citrate, and the formation of complexes among citrate, Fe and Co ions.